FIGURATIVE LANGUAGE IN THE SELECTED SONGS IN THE ALBUM “ONLY HUMAN” BY CALUM SCOTT - Tiara, Tiara; Weda, Sukardi; Burhamzah, Muftihaturrahmah (State University of Makassar, 2025)
This study aims to suppress the answers to the research questions. The objective of this study are: (1) To find out the type of figurative language used in the lyrics of Calum Scott songs. (2) To identify the meaning of the figurative language used in the lyrics of Calum Scott selected songs. This research using a qualitative descriptive. The data sources of this research are several Calum Scott song lyrics contained in the album “ Only Human”, namely